Therapeutic potential of NR4A1 in cancer: Focus on metabolism - Deng, Shan; Chen, Bo; Huo, Jiege; Liu, Xin (Frontiers in Oncology, 2022)
Metabolic reprogramming is a vital hallmark of cancer, and it provides the necessary energy and biological materials to support the continuous proliferation and survival of tumor cells. NR4A1 is an orphan nuclear receptor that belongs to nuclear subfamily 4 (NR4A) receptors. NR4A1 plays an important role in many malignant carcinomas, such as colorectal cancer, breast cancer, melanoma, and hepatocellular cancer, to regulate cell growth, apoptosis, metastasis. Recent reports shown that NR4A1 exhibits unique metabolic regulating effects in cancers. This receptor was first found to mediate glycolysis via key enzymes glucose transporters (GLUTs), hexokinase 2 (HK2), fructose phosphate kinase (PFK), and pyruvate kinase (PK). Then its functions extended to fatty acid synthesis by modulating CD36, fatty acid-binding proteins (FABPs), sterol regulatory element-binding protein 1 (SREBP1), glutamine by Myc, mammalian target of rapamycin (mTOR), and hypoxia-inducible factors alpha (HIF-1α), respectively. In addition, NR4A1 is involving in amino acid metabolism and tumor immunity by metabolic processes. More and more NR4A1 ligands are found to participate in tumor metabolic reprogramming, suggesting that regulating NR4A1 by novel ligands is a promising approach to alter metabolism signaling pathways in cancer therapy. Basic on this, this review highlighted the diverse metabolic roles of NR4A1 in cancers, which provides vital references for the clinical application.